Clinical Practice Guideline for Enteroscopy. Issue 5 (9th June 2017) - Yamamoto, Hironori; Ogata, Haruhiko; Matsumoto, Takayuki; Ohmiya, Naoki; Ohtsuka, Kazuo; Watanabe, Kenji; Yano, Tomonori; Matsui, Toshiyuki; Higuchi, Kazuhide; Nakamura, Tetsuya; Fujimoto, Kazuma
Abstract : Management of small bowel diseases has evolved since the advent of capsule endoscopy (CE) and balloon‐assisted enteroscopy (BAE). One of the most common indications for enteroscopy is obscure gastrointestinal bleeding (OGIB), followed by small bowel stenosis, tumors, and inflammatory bowel disease. Although enteroscopes have been regarded as useful tools, correct guidelines are required to ensure that we manipulate these enteroscopes safely and efficiently in clinical practice. Herein, the Japanese Gastroenterological Endoscopy Society has developed 'Clinical Practice Guidelines for Enteroscopy' in collaboration with the Japanese Society of Gastroenterology, the Japanese Gastroenterological Association, and the Japanese Association for Capsule Endoscopy. These guidelines are based on the evidence available until now, but small bowel endoscopy is a relatively new technology, so the guidelines include recommendations based on a consensus reached among experts when the evidence has not been considered sufficient. These guidelines were not designed to be disease‐based, but focus on how we should use small bowel CE and BAE in everyday clinical practice.